Challenges of Translating Slang Expressions in American Song Lyrics of the 21st Century into the Arabic Language - Batubara, Junita; Syarifudin, Achmad; Syathroh, Isry Laila; ., Herman; Yasaviyevna, Dina Shigabutdinova; Al-Awawdeh, Nabil (International Journal of Membrane Science and Technology, 2023)
Slangs are phrases that have strong roots in the culture of a given social and cultural stratum; translating them is challenging. Slang is a kind of daily socio-linguistic manifestation that emerges from a particular socio-cultural or socio-economic group's efforts to codify its members' ideology or mental projections. Slang refers to a language or set of words that are widely used but seldom defined. This study is an Arabic translation of slang used in 21st-century American songs. The research also examines how the slang was translated and the attributes that made them practical communication tools. Arabic speakers learning American English will benefit most from this concentration on slang and its context. The analysis is carried out through the thematic analysis method based on an apparent qualitative study. Twenty (20) slang terms borrowed from 21st-century American pop songs were adapted to be translated into Arabic. The study's data consists of slang expressions in the song lyrics of two American hip-hop/rap singers, Eminem and Wiz Khalifa. Marshal Mathers II by Eminem (2013) and Khalifa by Wiz Khalifa (2016) were picked as the only albums by each artist. To communicate with native Arabic speakers, the researcher modified the English-Arabic Translator used for superficial translation. Functional equivalents, social equivalents, modulations, substitution, and paraphrases are the main translation strategies adopted in translating the selected slang into formal Arabic. Based on the thematic evaluation, it was discovered that paraphrasing is the most effective strategy for translating American slang into Arabic. Consequently, the research shows that the meanings of slang terms are affected by context and situational variability. The conclusion is that slang plays a significant part in a conversation. To utilize it fully, learners must be familiar with their contexts and interpretations.